412 Germ and somatic cell interactions during oocyte development and maturation. (30th November 2020) - Perecin, Felipe
Abstract: Ovarian follicle development and oocyte competence acquisition is dependent upon continuous interactions between the somatic cells and the oocyte. Interactions between these cell types include bidirectional paracrine signaling and the exchange of small molecules, such and amino acids and cyclic nucleotides, through gap junctions located at the end of transzonal projections (TZPs). In the last decade, additional mechanisms of cell-to-cell interactions within the ovarian follicle were described. These mechanisms include the movement of small extracellular vesicles (EVs) within the follicular fluid and the delivery of its cargo to target cells; and the exchange of large molecules transiting from the cumulus cells to the oocytes via transzonal projections. Here, I will describe the investigations about these novel communication systems in the bovine ovarian follicle. The topics will include the content of EVs transiting in the bovine follicular fluid and its role regulating signaling pathways associated with oocyte competence, and the movement of large molecules from cumulus cell to the oocyte such as messenger RNAs and fatty acids. Finally, dysregulations of such communications mechanisms under in vitro culture conditions will also be reviewed. Emphasis will be given on the lipid metabolism in the cumulus-oocyte complex and lipid accumulation mediated by transzonal projections and fatty acid binding proteins in oocytes undergoing in vitro maturation.